Formation of parameters of elements of hoisting and transport machines of manipulator type at the design stage - Bakay, B.Ya.; Hobela, V.M. (Forestry, Forest, Paper and Woodworking Industry, 2018)
Techniques and principles of designing loading machines of manipulator type are diverse and complex. Modern methods of designing loading machines and their individual elements are implemented on the basis of analysis of the technological process in which they are expected to operate. Also, to reduce the cost and reduce the time of design, manufacture and implementation of special purpose loading machines, increase their maintainability and facilitate the acquisition of many domestic and foreign companies began to use unit-modular design. This approach allows to divide the loading machines of the manipulator type into simpler functional elements, the pliability of which is easy to determine by the methods of the theory of resistance of materials. To transition from the pliability of such individual elements to the pliability of loading machines in general, use the matrix of transmission relations obtained in the process of force analysis and calculation of elements for accuracy. The aggregate-modular principle can be one of the main principles of realization of loading machines of manipulator type. This principle makes it possible, given the limited number of normalized elements to create a specialized design of the loading machine, which best meets the requirements of a particular technological task and there is no redundancy. This approach in each case allows to reduce the time of development and design of specialized hoisting machines of the manipulator type, increase reliability due to the durability of the elements included in it, reduce the cost of production by reducing the range of parts and components. It is offered to carry out formation of constructive parameters of elements of loading machines of manipulator type at a design stage by carrying out the power analysis and calculation of elements on accuracy. This improves the known design solutions, making them more suitable for practical application.